Geologi Daerah Muntok dan Potensi Granit Menumbing Sebagai Sumber Uranium (U) dan Thorium (Th) - Saksama, Kurniawan Dwi; Ngadenin, Ngadenin (BRIN Publishing, 2013)
In the West Bangka there are some granites namely Menumbing, Pelangas, Tempilang, and Jebus granite. The granites is granite tin belt that stretches from Thailand-Malaysia-Bangka Belitung. Granite tin belt or granite source of tin (cassiterite) can act as a source of U and Th. Aims of the study is to find out the informationon the geology of Muntok area and its surrounding and to determine the potency of Menumbing granite as a source of U and Th. The methods used is surface geological mapping in Muntok areas and its surrounding with scale 1 : 25.000, measurement grade of uranium and thorium in Menumbing granite areas and petrographic and grain size analysis of sample of Menumbing granite. Determination of granites a source of U and Th is based on content of radioactive mineral, anomaly of U and Th, megascopic and microscopic observation of granite. Morphology of Muntok areas and its surrounding is denudasional undulating plains to hills with an elevation ranging from 0 to 455 meters. Sratigraphy of research areas from old to young is metasandstone units, granite intrusion of Menumbing and alluvial. Evolving fault is a fault trending West-East. Based on the presence of radioactive minerals, grade of U and Th as well as the type of granite, it was concluded that the Menumbing granite is a source of Th and not sources of U.